Analysis of organic farming’s economic viability at different subsidy levels - Kormosné Koch, Krisztina (Acta Agraria Debreceniensis, 2008)
Applying a data-collection-based economic model, I analyzed the economic viability of organic farming at different subsidy levels. The database is concentrated on the Hortobagy region. On the basis of data, I built an average sized and operated organic farm model with both arable land cultivation and animal keeping activities. The analysis of viability is based on gross profit calculation and compared with the criteria of the long-term economic viability, determined by the author. This study summarizes the most important results of the analysis.